Is Leishmaniasis donovani elimination feasible in Bhutan? A review of current prevention and control mechanisms in Bhutan - Tashi Tobgay; Sithar Dorjee; Ambika Pradhan; Tenzin Wangdi; Tobgye Drukpa; Rinxin Namgye; Guofa Zhou; Nadira D. Karunaweera Karunaweera (Bhutan Health Journal, 2021)
Leishmaniasis is a neglected tropical disease with an annual estimated 700,000 to 1 million new cases globally. The diseases affect the rural community and people living in poverty. It is transmitted by female phlebotomine sand-fly; a tiny 2–3 mm long insect vector. Along with the regional countries, Bhutan has embarked on the elimination goal. However, several challenges lies ahead on its path to elimination. There is no elimination strategy and actions. The reporting, surveillance system, control and prevention mechanisms are inadequate. Further, there is lack of knowledge among the health care providers that impedes elimination goals. Therefore, if Bhutan is serious about its elimination goal, all the gaps and current challenges needs to be addressed appropriately.